Commentary: Microbial panaceas: does development have the answer? – reflections on Cowan, Dinan, & Cryan (2020). (15th January 2020) - Callaghan, Bridget
Abstract : Is the microbiome a promising adjunct, a potential panacea, or a distraction from feasible treatments for neurodevelopmental disorders? Taking a developmental approach may get us closer to understanding the data and give us pause in trying to translate this nascent field to the clinic right now. Abstract : Read the full article at doi: 10.1111/jcpp.13156